Caracterização físico-química e hidrólise enzimática da casca da Myrciaria jabuticaba (Vell) Berg (jabuticaba Sabará) - (:unkn) unknown (Universidade Estadual de Goiás, 2016)
With the growing interest in the use of renewable natural resources for the production of biofuels, lignocellulosic materials has become a major target for researchers. The use of agro-industrial waste as a source of lignocellulosic materials is a viable alternative to the use of these low-cost and widely available materials. In this work were determined the physicochemical characteristics of jabuticaba shell, the material had a composition of 20.63% cellulose, 13.69% hemicellulose, lignin 24.33% and 41.34% of holocelulose. The amount of proteins, lipids, total sugars, moisture and ash were respectively in g / 100g bark: 9.82, 1.97, 66.85, 79.61 and 0.593. enzymatic hydrolysis with a combination of cellulase enzymes and β-glucosidase 20U / 10U in jabuticaba peel treated and not treated with sulfuric acid 1% was obtained (w / v) and evaluated enzymatic hydrolysis at different reaction times (24, 48, 72, 96 and 120 hours). It was found that the time 72 h showed the best results in expression sugars.
Keywords: Materiais lignocelulósicos; Hidrólise enzimática; Prétratamento; Lignocellulosic materials; Enzymatic hydrolysis; Pretreatment; CIENCIAS EXATAS E DA TERRA::QUIMICA; QUIMICA::QUIMICA ORGANICA